Differentiating between cold agglutinins and rouleaux: a case series of seven patients. (March 2018) - Heath, Michele; Walker, Julie; Barbeito, Atilio; Williams, Adam; Welsby, Ian; Maxwell, Cory; Daneshmand, Mani; Haney, John; Hoffman, Maureane
We present a case series of seven patients with suspected cold agglutinin antibodies, discovered after initiation of bypass. Laboratory analysis of blood samples intraoperatively determined the cause of the aggregation to be rouleaux formation in three of the patients and cold agglutinins in the other four.